Advances in the crosstalk between maternal separation and voluntary ethanol consumption and effects on reproduction - Teixeira, Giovana Rampazzo [UNESP]; Martins, Otávio Augusto [UNESP]; Kremer, Rafael; Veras, Allice Santos Cruz [UNESP]; Pinheiro, Patricia Fernanda Felipe [UNESP]; Mello-Junior, Wilson [UNESP]; Martinez, Francisco Eduardo [UNESP] (Elsevier, 2022)
Maternal separation (SM) is an event caused by early stress and may be associated with behavioral changes and vulnerabilities, enhancing ethanol consumption in adulthood. The aim of the study was to evaluate whether MS potentiates the effects of ethanol ingestion on physiological hormone regulation and its interference in testicular and epididymal morphofunctional aspects in voluntary ethanol-consuming rats. Therefore, for the first time, we investigated the effect of maternal separation and ethanol consumption in adulthood and for this we used free choice ethanol-consuming strains. Responses of metabolic and hormonal parameters were also addressed, as well as their effects on reproductive function. In summary, MS promoted an increase in voluntary ethanol consumption in UChA and UChB animals. There was an influence of MS on the increase of circulating corticosterone and testosterone in UChB animals (high-ethanol-preferring 10 % v/v). MS performed in the hyporesponsive period to stress promoted an increase in glucose and circulating lipids, as well as a reduction in lactate dehydrogenase levels. Daily sperm production and transit time through the epididymis in UChB animals were increased by MS. Together, these findings show that MS potentiates the effects of ethanol ingestion and promotes an imbalance in plasma hormone concentrations, interfering with the reproductive functional imbalance of ethanol-consuming rats.
Keywords: Alcohol-induced disorders; Corticosterone; Early-life stress; Pituitary-adrenal system